Pride and Shame in Child and Family Social Work : Emotions and the Search for Humane Practice - Gibson, Matthew (Book collections on Project MUSE., 2019)
Examining the implications of the emotional experiences of shame and pride in the context of professional practice and the relationship between the individual, the family and the state, the book calls for a more humane form of practice, rooted in more informed policies that take in to consideration the realities and frailties of the human experience.